2018
DOI: 10.1097/gox.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Antegrade Posterior Interosseous Flap for Nonhealing Wounds of the Elbow: Anatomical and Clinical Study

Abstract: Background:The posterior interosseous artery (PIA) flap has been widely reported to cover defects at the dorsal aspect of the hand. However, the use of this flap to cover elbow defects has been rarely reported. The purpose of this study was to analyze the anatomical feasibility of the PIA flap to cover elbow soft-tissue defects and, additionally, to review the clinical outcomes of patients treated with this flap.Methods:An anatomical study was performed on 14 cadaveric specimens to assess the number of PIA per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…No extensor tendon palsies, which have been reported previously with this technique, and no complications at the donor site were reported in the postoperative period. 9…”
Section: Resultsmentioning
confidence: 99%
“…No extensor tendon palsies, which have been reported previously with this technique, and no complications at the donor site were reported in the postoperative period. 9…”
Section: Resultsmentioning
confidence: 99%
“…Microsurgical techniques for vascularized bone grafts, such as the vascularized fibula bone grafts, are demanding. Local pedicled vascularized flaps offer several advantages over free flaps, including less donor-site morbidity, an operative field limited to one upper extremity; less technically demanding and, therefore, skillsets that are achievable by most hand surgeons (Costa et al., 2001; Jakubietz et al., 2019; Zaidenberg et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the PIV, the ulnar periosteal pedicle flap has been successfully used in different ways, by altering its flow (anterograde, proximally based or retrograde, distally based) and soft tissue contents (fascia, fascio-cutaneous, osteo-fascio-cutaneous) (Barın et al., 2019; Jakubietz et al., 2019; Tiengo et al., 2016; Zaidenberg et al., 2018). In our cohort, we have found that the flap was versatile to cover small and medium defects in the forearm without any tension in the pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, the soft tissue coverage remains a major aspect during the treatment of an infection about the elbow. The posterior interosseous artery (PIA) flap has been described as an alternative option for soft tissue defects smaller than 40cm2, 5 its advantages include that the PIA is very constant, donor site morbidity is scarce and does not require advanced microsurgical technique. Anconeus, brachioradialis, latissimus dorsi, and flexor carpi ulnaris muscle flaps as well as radial forearm and lateral arm fascio-cutaneous flaps are some of the more commonly reported flaps for reconstruction.…”
Section: Introductionmentioning
confidence: 99%